The Impact of Transit-Oriented Development on Fast-Urbanizing Cities: Applied analytical study on Greater Cairo Region - Mohamed Kafrawy; Sahar Attia; Heba Allah Khalil (Journal of Contemporary Urban Affairs, 2022)
Transportation has always been the backbone of development. Transit-oriented development (TOD) has been theorized, piloted and expanded increasingly in the past few decades. In this regard, this paper investigates the relationship between urban development, the transportation process, and the required implementation guidelines within fast-urbanizing cities, such as Cairo. After reviewing different related sustainable development theories, the study investigates pioneering case studies that have applied TOD and provided adequate implementation frameworks. The authors then extract and compare a set of required policies. The current Egyptian development paradigm is then discussed in relation to these enabling policies, focusing on Greater Cairo Region, Egypt. The authors debate previous development plans, progress, and newly proposed ones, focusing on the transportation process as the means for development. The study concludes with a set of required guidelines to ensure the integration of transportation with land-use planning, thus ensuring a more prosperous and inclusive urban development.